Evaluation of rhabdomyolysis patients who opted for emergency services - Serdar Ozdemir; Oktay Ocal; Gokhan Aksel (İstanbul Kuzey Klinikleri, 2017)
INTRODUCTION[|]Rhabdomyolysis is a clinical and biochemical syndrome caused by skeletal muscle injury. Our aim was to contribute to the existing data on rhabdomyolysis in our country by evaluating the etiologic, demographic, and clinical features of rhabdomyolysis patients who applied to a tertiary hospital emergency department.[¤]METHODS[|]We retrospectively evaluated the data of patients who applied to the tertiary hospital emergency department from January 2015 to January 2016. The study population comprised patients admitted to the emergency department of our hospital with creatinine kinase levels above 5000 U/L at admission. The data of all cases that were included in the study were scanned by the researchers using the hospital's computer-based data recording system. Age, sex, creatine kinase levels, complaints, etiology, whether or not acute renal failure developed, hospitalization and discharge status, and clinic of hospitalization were screened for all patients.[¤]RESULTS[|]The creatine kinase levels of the patients at admission ranged from 5052 to 59140 U/L [median 7882 U/L (IQR: 7840)]. The most frequent (23.5%) cause of admission was extremity pain. The most common reason (19.6%) in the etiology was exercise. Twenty-one patients (41.1%) were admitted to clinics, and 1 patient (1.9%) died. Acute renal failure was observed in 4 patients (8.8%).[¤]DISCUSSION AND CONCLUSION[|]Rhabdomyolysis is a clinical syndrome that can be life-threatening owing to muscle destruction. Although it is suspected after a traumatic injury, it should also be considered when other potential symptoms are observed. All clinicians should be aware of its common causes, diagnosis, and treatment options.[¤]